A Morphometric Analysis of Starch Granules from Two Dioscorea Species - Sara Rickett; Lisbeth A. Louderback; Adrian V. Bell (Plants, 2025)
Dioscorea is a genus comprising over 600 species, many of which possess edible tubers that are commonly referred to as yams. While Dioscorea is a significant crop across the globe, it holds a unique cultural significance to the people of Tonga in western Polynesia. Presently, Dioscorea is known for its essential role in festivals and ceremonies, as well as for its nutritional contributions to Tongan diets. To understand and to assess the significance of Dioscorea in the distant past, however, archeologists rely on plant residues (e.g., starch granules) preserved on ancient tools. This study provides the necessary first step in archeological starch analysis by examining the granule morphometrics of two culturally significant Dioscorea species, D. alata and D. bulbifera from Tonga. Tubers from three individuals of each species were collected on the island of Vava’u and processed for starch granule extraction and analysis. Morphometric characteristics, including two novel that describe shape (eccentricity ratio and hilum angle), were measured on approximately 300 granules per species. When statistically compared, these novel characteristics allow D. alata and D. bulbifera to be readily distinguished from one another, and therefore increase confidence in assigning archeological granules to a specific taxon.